Biogenic Silver Nanoparticles as a Strategy in the Fight Against Multi-Resistant Salmonella enterica Isolated From Dairy Calves - Estevez, María Belén; Casaux, María Laura; Fraga, Martín; Faccio, Ricardo; Alborés, Silvana (Frontiers in Bioengineering and Biotechnology, 2021)
Infectious diseases are one of the most important health problems worldwide, one of the main causes being the development of multi-resistant microorganisms. Likewise, the zoonotic potential of some pathogens and their ability to transfer resistance mechanisms, reduce the therapeutic options in both humans and animals. Salmonella enterica is an important pathogen that affects a wide range of animal species and humans, being Salmonella Typhimurium one of the most frequent serotypes affecting cattle, causing enteritis, diarrhea, and septicemia. The search for alternative therapeutic approaches has gained importance since the emergence of multidrug resistance to antibiotics and periodic outbreaks of salmonellosis. In this sense, the discovery of new drugs and the development of new strategies, such as the use of nanoparticles with antimicrobial activity, are very promising. The aim of this work was the extracellular production of biogenic silver nanoparticles using fungal extracts and the evaluation of their antimicrobial activity against resistant and multi-resistant Salmonella Typhimurium strains. We here demonstrated the potential of the biogenic nanoparticles as effective bacteriostatic and bactericidal agents for use in biomedical applications. In addition, Confocal Raman Microscopy and Atomic Force Microscopy were used to advance the understanding of the antimicrobial mechanism of biogenic nanoparticles against these pathogenic strains, the results of which suggested that the nanoparticles produced damage in several bacterial cell structures.